Selenoproteins and cardiovascular stress - Rose, Aaron H.; Hoffmann, Peter R. (Thrombosis and Haemostasis, 2015)
Dietary selenium (Se) is an essential micronutrient that exerts its biological effects through its incorporation into selenoproteins. This family of proteins contains several antioxidant enzymes such as the glutathione peroxidases, redox-regulating enzymes such as thioredoxin reductases, a methionine sulfoxide reductase, and others. In this review, we summarise the current understanding of the roles these seleno proteins play in protecting the cardiovascular system from different types of stress including ischaemia-reperfusion, homocysteine dysregulation, myocardial hypertrophy, doxirubicin toxicity, Keshan disease, and others.
Keywords: Cardiovascular; heart; oxidative stress; selenium; selenoproteins